Scattering and Bound State Solutions of the Yukawa Potential within the Dirac Equation - F. Pakdel; A. A. Rajabi; M. Hamzavi (Advances in High Energy Physics)
In the presence of spin symmetry case, we obtain bound and scattering states solutions of the Dirac equation for the equal scalar and vector Yukawa potentials for any spin-orbit quantum number κ. The approximate analytical solutions are presented for the bound and scattering states and scattering phase shifts.